2020
DOI: 10.1111/anu.13209
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of tributyrin, alone and in combination with fructooligosaccharide in high soybean meal diets for shrimp ( Litopenaeus vannamei ): Effects on growth, innate immunity and intestinal morphology

Abstract: A 6-week feeding trial was conducted to investigate the effects of adding tributyrin (TB), alone and in combination with fructooligosaccharides (FOS) in high soybean meal (SBM) diets on growth performance, innate immunity and intestinal morphology of shrimp (Litopenaeus vannamei). Six isonitrogenous and isolipidic diets were formulated: positive control diet (PC, containing 250 g/kg fishmeal (FM) and 285 g/ kg SBM), control diet (C, containing 125 g/kg FM and 439.2 g/kg SBM) and four experimental diets with 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 66 publications
2
20
1
Order By: Relevance
“…The present study showed that the addition of TB to high CRM diets tended to improve the growth performance of grass carp so that the addition of 1000 mg/kg TB presented the same growth as compared with the PC group. These results are consistent with results obtained from common carp (Xie et al, 2021) and shrimp (Liu et al, 2021). This result may be due to the fact that TB can improve the intestinal health of fish.…”
Section: Ta B L Esupporting
confidence: 92%
See 1 more Smart Citation
“…The present study showed that the addition of TB to high CRM diets tended to improve the growth performance of grass carp so that the addition of 1000 mg/kg TB presented the same growth as compared with the PC group. These results are consistent with results obtained from common carp (Xie et al, 2021) and shrimp (Liu et al, 2021). This result may be due to the fact that TB can improve the intestinal health of fish.…”
Section: Ta B L Esupporting
confidence: 92%
“…In this study, the addition of TB to a high CRM diet increased the levels of AKP, C3, C4 and IgM in the serum, which indicated that TB can improve immune function of grass carp. Similarly, various previous studies have reported that TB supplementation in feed can also increase the production of immunoglobulins (Liang et al, 2021) and the AKP activity (Liu et al, 2021). A possible reason is that TB can improve immune function by controlling the inflammatory response and regulating the expression of anti-inflammatory factors (Leonel et al, 2013).…”
Section: Ta B L Ementioning
confidence: 74%
“…However, not all probiotics can achieve positive benefits in aquatic animals because many probiotics originated from milk, cheese or other terrestrial sources (Doan et al, 2018). Studies have shown that fish fed low SBM diet showed better growth performance, health status and intestinal microbiota than those fed high SBM diet (Li, Zhang, et al, 2012;Li, Ai, et al, 2012;Li et al, 2014;Zhang et al, 2016), and healthy gut microbiota is strongly associated with improvements in host health and well-being (Hoseinifar et al, 2018;Liu et al, 2021). In the present study, we isolated and selected five host-associated potential probiotic strains and found that they only occur or present in a high proportion in the intestine of L. japonicus fed SBM-free diet, indicating that the strains might benefit the growth and health of L. japonicus.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, serum immune parameters directly reflected the health status of organisms (Liu et al, 2021). Serum immunoglobulin and complement 3 (C3) are the primary components of the immune system, which play critical roles in alerting the host immune system in the presence of potential pathogens as well as their clearance, and IgM is the main immunoglobulin present in fish (Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation